RANCANG BANGUN MEJA DAN KURSI BELAJAR SECARA ERGONOMI DIBENGKEL LAS NUANSA TEKNIK LUBUK BUAYA PADANG - Tri Ernita; Irawanto . (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2018)
The study desk and chair is a very important supporting tool in the implementation of teaching and learning. To anticipate the existence of unsuitable between table and chair with student body size, it will be designed to build desk and chairs study ergonomically in accordance with the size of the human body. So the purpose of the research of this task ahir is to make ergonomic desk design and chair and know the costs incurred to make ergonomic desk and chair learning.The result of this research is the new study table and chair made of iron pipe and has 37cm holder width,39cm holder length,overall seat height 90cm,43cm seat height,74cm overall seat lengt, 55x42cm table width, 39x37cm bookcase,16cm tall bookcase, 13x37cm footstool, 23cm high footing, foam backrest and 7cm holder. As for the total cost of making desks and chairs studied this final result is Rp.815.500.